HUBUNGAN PARTISIPASI MASYARAKAT UPPKA TERHADAP PENINGKATAN PENDAPATAN DI KAMPUNG KB BERKAH BERSAMA - Wulandari, Putri; Arifandy, M. Imam; Darusman; Soim, Muhammad; Yefni; Antin, Titi; Kodarni (Universitas Riau, 2025)
This study was conducted to examine the relationship between community participation in the Family Income Improvement Program for Acceptors (UPPKA) and the increase in community income in Air Dingin Sub-district. The research was driven by the need to assess how far community involvement in the UPPKA program influences income improvement. Employing a quantitative research design, data were collected through questionnaires distributed to 19 respondents who are active members of the UPPKA program. Data analysis was performed using the Kendall’s Tau-b correlation test to determine the strength and direction of the relationship between the variables. The correlation interpretation was conducted with reference to the Correlation Coefficient interpretation table and processed using IBM SPSS Statistics version 23. The results indicate a positive and statistically significant relationship between community participation in the UPPKA program and the increase in community income, with a significance value of 0.014 (p < 0.05) and a correlation coefficient of 0.547, categorized as a moderately strong relationship.